The Use Of Audiovisual Media In Improving The Forward Roll Gymnastics Learning Outcomes - Awaluddin; Dadi Surjadi (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2021)
The purpose of this study was to determine the effect of Audio Visual learning media on learning outcomes of forward roll gymnastics for students. This type of research is a experimental research with a one group pretest posttest design with a sample of 23 students in SMP Negeri 3 Pujananting, Barru Regency. The results of this study obtained the value of floor gymnastics learning outcomes with the mean of pretest + SD (80 + 7.38) and the mean of posttest + SD (85 + 7.48). Test results of the paired t-test (p=0.000) showed that there was a significant effect of audio-visual learning media on the learning outcomes of forward roll exercise before and after treatment. It can be concluded that the use of audio visual media can improve learning outcomes for forward roll gymnastics.